Politeness and Hostility in Anime Fandom: A Sociolinguistic Study of YouTube Comments - Achmad, Zakaria; Lubis, Reza Dian Irawan; Aria, Fahri Mulia; Rangkuti, Rahmadsyah (Universitas Pahlawan Tuanku Tambusai, 2025)
Online fandom communities represent one of the most dynamic and linguistically diverse environments on social media, where politeness and hostility coexist within the same communicative space. This study investigates the realization of illocutionary speech acts in YouTube comment sections, focusing on interactions within anime fandom debates. Using Searle’s classification of illocutionary acts and Brown and Levinson’s politeness theory, the research analyzes 200 comments collected from popular anime-related videos between 2023 and 2024. The findings reveal that expressive and representative acts dominate the discourse, functioning both as strategies of solidarity and as tools of verbal conflict. Politeness emerges through acts of appreciation, humor, and defense of shared fandom identity, while hostility is expressed via sarcasm, ridicule, and impoliteness. The study concludes that the coexistence of these two forces reflects the social negotiation of identity and belonging within online fan cultures.